Accumulation of cell‐penetrating peptides in large unilamellar vesicles: A straightforward screening assay for investigating the internalization mechanism. Issue 5 (September 2015) - Swiecicki, Jean‐Marie; Di Pisa, Margherita; Burlina, Fabienne; Lécorché, Pascaline; Mansuy, Christelle; Chassaing, Gérard; Lavielle, Solange
ABSTRACT: The internalization of cell‐penetrating peptides (CPPs) into liposomes (large unilamellar vesicles, LUVs) was studied with a rapid and robust procedure based on the quenching of a small fluorescent probe, 7‐nitrobenz‐2‐oxa‐1, 3‐diazole (NBD). Quenching can be achieved by reduction with dithionite or by pH jump. LUVs with different compositions of phospholipids (PLs) were used to screen the efficacy of different CPPs. In order to "validate" the composition of the membrane models, a control cationic peptide, which does not enter eukaryotic cells, was included in the study. It was found that pure DOPG or DOPG within ternary mixtures with cholesterol are the most appropriate models for studying CPP translocation. An anionic lipid, such as DOPG, is required for the adsorption of the basic peptides on the surface of LUVs. In addition, it acts as transfer agent through the lipid bilayer. A fluid phase and/or the presence of phase defects also appear mandatory for the internalization to occur. The neutralization of charges within an inverted micelle demonstrated in the case of DOPG and also proposed for a ternary mixture of PLs might not be the only mechanism for the CPP translocation. Finally, it is shown that oleic acid facilitates the entry inside LUVs in gel phase of a series of cationic peptides including CPPs and also the negative control peptide PKCi. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 533–543, 2015.